Modified musculofascial lengthening technique for submuscular ulnar nerve transposition in cubital tunnel syndrome - Sang-Pil So; Won Sun Lee; KiHyeok Ku; Young Ho Shin; Jae Kwang Kim (PLoS ONE, 2025)
Objective Cubital tunnel syndrome is a common peripheral neuropathy of the upper extremity. Anterior transposition of the ulnar nerve is an established surgical treatment option for this condition. This study aimed to introduce a novel musculofascial lengthening technique that uses only a portion of the flexor-pronator muscle mass for submuscular anterior transposition of the ulnar nerve and investigate its clinical outcomes. Methods We evaluated 28 patients (29 cases; 1 patient had bilateral involvement) diagnosed with cubital tunnel syndrome who were treated with surgical decompression and submuscular anterior transposition of the ulnar nerve using our novel technique. Mean follow-up was 19.1 months (range, 12–31). Patient-reported outcomes were assessed using the Boston Carpal Tunnel Questionnaire (BCTQ), Disabilities of the Arm, Shoulder, and Hand (DASH) Questionnaire, and numeric rating scale (NRS) for pain. Objective outcomes including light touch perception, static two-point discrimination, and grip strength were also assessed. Modified Bishop score and postoperative complications were also evaluated. Results BCTQ symptom severity and functional status scores, DASH score, and NRS for pain score showed significant improvement after surgery. Light touch perception, static two-point discrimination, and grip strength also significantly improved after surgery. All patients showed excellent or good results according to the modified Bishop scoring system. No recurrence or complications occurred. Conclusion Our novel musculofascial lengthening technique that uses only a portion of the flexor-pronator muscle mass for submuscular anterior transposition of the ulnar nerve reliably achieves good results with minimal complications in patients with cubital tunnel syndrome.